The new art history a critical introduction - Harris, Jonathan (Routledge, 2001)
The New Art History provides a comprehensive introduction to the fundamental changes which have occurred in both the institutions and practice of art history over the last thirty years. Jonathan Harris examines and accounts for the new approaches to the study of art which have been grouped loosely under the term the new art history. He distinguishes between these and earlier forms of radical or critical analysis, explores the influence of other disciplines and traditions on art history, and relates art historical ideas and values to social change. Structured around an examination of key texts by major contemporary critics, including Tim Clarke, Griselda Pollock, Fred Orton, Albert Boime, Alan Wallach and Laura Mulvey, each chapter discusses a key moment in the discipline of art history, tracing the development and interaction of Marxist, feminist and psychoanalytic critical theories.